2021
DOI: 10.1515/jcim-2020-0175
|View full text |Cite
|
Sign up to set email alerts
|

Preventive aspect of ayurveda and yoga towards newly emerging disease COVID-19

Abstract: The ongoing coronavirus pandemic is caused by severe acute respiratory syndrome coronavirus 2 (SARS CoV 2) and unique in various facets. The earlier experience from the past severe acute respiratory syndrome (SARS) epidemics seem to be insufficient and there is need for better strategies in public health and medical care. Ayurved & Yog are well known for their preventive and therapeutic aspect, but not getting utilized properly for prevention of Covid 19 crisis which may also be helpful as supportive thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…This result was not astonishing due to the restric- tion of some types of sports or physical activity, which could not be practiced in the pandemic anymore, like team sports or swimming. The importance of yoga as a preventive strategy in the pandemic was also verified by a review of Sawant, Zinjurke, and Binorkar (2021). Furthermore, more digitalized fitness programs were chosen, which is in line with a study of Parker et al (2021) who reported higher physical activity of those people who practice sport or physical activity with the help of a digitized form.…”
Section: Change Of Type Of Sport and Physical Activity During The Coronavirus Pandemicmentioning
confidence: 95%
“…This result was not astonishing due to the restric- tion of some types of sports or physical activity, which could not be practiced in the pandemic anymore, like team sports or swimming. The importance of yoga as a preventive strategy in the pandemic was also verified by a review of Sawant, Zinjurke, and Binorkar (2021). Furthermore, more digitalized fitness programs were chosen, which is in line with a study of Parker et al (2021) who reported higher physical activity of those people who practice sport or physical activity with the help of a digitized form.…”
Section: Change Of Type Of Sport and Physical Activity During The Coronavirus Pandemicmentioning
confidence: 95%
“…Yoga practice has been reported as improving chronic obstructive pulmonary disease (COPD) [ 43 ], namely through the increase of tolerance to exercise [ 44 ]. COVID-19 disease has a high mortality due to lung infection, so yoga can be effective in preventing premature death of COVID-19 related lung infection [ 45 ].…”
Section: Why Should We Use Yoga For Covid-19 Disease?mentioning
confidence: 99%
“…Anuloma-viloma, one type of pranayama characterized by alternating breathing through the nostrils, removes minor blockages, balances the flow of breath in both nostrils, and decreases heartbeat and blood pressure [ 45 ]. Sudarshan Kriya Yoga (SKY), an advanced controlled cyclic rhythmic breathing technique, is able to augment overall immunity against various microbial, fungal, and viral infections [ 31 ].…”
Section: How To Use Yoga For Covid-19 Patientsmentioning
confidence: 99%
“…Thus, the definition of health has been updated to include physical, mental, social and spiritual wellbeing. TCAM covers a broad list of practices, including Qigong, Tai Chi, meditation, mindfulness, and yoga, which could be seen as complementary medical tools positively reported in the literature as useful in the prevention and amelioration of several health conditions, including those related to the respiratory system [ 6 , 7 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%